Carrying out Scientific and Applied Researches Calls for Management and Progress Modernization within the Space Research and Technologies Institute - Getsov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The contemporary science grows at enormously accelerated rate. In the present paper, the topicality of both scientific work and applied researches is emphasized. In addition, the author’s comprehension is indicated as concerns the necessity of both structure and activity modernization of the Space Research and Technologies Institute. A particular programme for management and advance of the Institute is suggested.